Delivering primary health care as envisioned: A model of health and well-being guiding community-governed primary care organizations. Issue 3 (14th May 2018) - Rayner, Jennifer; Muldoon, Laura; Bayoumi, Imaan; McMurchy, Dale; Mulligan, Kate; Tharao, Wangari
Abstract : Purpose: For over 40 years, Canadian and international bodies have endorsed comprehensive primary health care (PHC), yet very little work has been done to describe how services and programs are delivered within these organizations. Because health equity is now of greater interest to policy makers and the public, it is important to describe an evidence-informed framework for the delivery of integrated and equitable PHC. The purpose of this paper is to describe the development of a "Model of Health and Well-being" (MHWB) that provides a roadmap to the delivery of PHC in a successful network of community-governed PHC organizations in Ontario, Canada. Design/methodology/approach: The MHWB was developed through an iterative process that involved members of community-governed PHC organizations in Ontario and key stakeholders. This included literature review and consultation to ensure that the model was evidence informed and reflected actual practice. Findings: The MHWB has three guiding principles: highest quality health and well-being for people and communities; health equity and social justice; and community vitality and belonging. In addition, there are eight attributes that describe how services are provided. There is a reasonable evidence base underpinning the all principles and attributes. Originality/value: As comprehensive, equitable PHC organizations become increasingly recognized as critical parts of the health care system, it is important to have a means to describe their approach to care and the values that drive their care. The MHWB provides a blueprint for comprehensive PHC as delivered by over 100 Community Governed Primary Health Care (CGPHC) organizations in Ontario. All CGPHC organizations have endorsed, adopted and operationalized this model as a guide for optimum care delivery.